1976
DOI: 10.1073/pnas.73.10.3613
|View full text |Cite
|
Sign up to set email alerts
|

Rous-sarcoma-virus-transformed fibroblasts having low levels of plasminogen activator.

Abstract: Several clones of transformed chick embryo fibroblasts infected with wild-type B77-C or Prague-C strain of Rous sarcoma virus have been isolated from sof agar suspension. These clones were screened for plasminogen activator activity by overlaying monolayer cultures with medium containing agar, casein, and chicken plasminogen. Twenty-three percent of all of the isolated clones showed little caseinolytic activity, 42% had intermediate activity, and 35% had high activity. Although the clones with low plasminogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
0

Year Published

1977
1977
1984
1984

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 30 publications
(22 reference statements)
2
10
0
Order By: Relevance
“…Protease activity has also been theorized to be the basis for growth of transformed cells in semisolid medium (2,7,10,11,16,22). Shin and coworkers demonstrated that tumorigenicity of virus-transformed cells in nude mice correlated specifically with anchorage-independent growth in vitro (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protease activity has also been theorized to be the basis for growth of transformed cells in semisolid medium (2,7,10,11,16,22). Shin and coworkers demonstrated that tumorigenicity of virus-transformed cells in nude mice correlated specifically with anchorage-independent growth in vitro (20).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies investigating the in vitro properties of chemically transformed hamster cells and human osteosarcoma cells show negative correlations between PA production and growth in semisolid agar (2,11). Cell clones selected from Rous sarcoma virus-transformed fibroblasts grown in soft agar show a variability in PA levels, but no difference in tumorigenic potential (22,23). It has also been shown that PA production is not sufficient to cause the absence of large external transformation-sensitive (LETS) protein (15).…”
Section: Discussionmentioning
confidence: 99%
“…Some normal cells have high levels of PA activity (1)(2)(3)28). For some clonal isolates of tumorigenic cell lines, no correlation between levels of PA activity and malignant transformation has been observed (8,15,27,31). Studies of a human epidermal carcinoma that metastasizes with a high efficiency into the organs of chicken embryos have shown that anchorage independence and serum independence inversely correlate with metastatic ability and tumorigenicity but directly correlate with enhanced levels of PA activity (19,20 (20).…”
mentioning
confidence: 99%
“…They have reported the appearance of plasminogen activator in cell cultures associated with oncogenic transformation, although Mott et al (1974) and Wolf & Goldberg (1976) revealed lack of correlation in established cell lines. Rosenthal et al (1977) and Nagy et al (1977) showed that fibrinolytic activity Qf cancer cells was very varied, and that it was closely associated with the passage history of the cultured cells.…”
Section: Discussionmentioning
confidence: 99%